Gangguan makan dan perilaku bunuh diri pada remaja: Sebuah tinjauan literatur - Hendrawati Hendrawati; Iceu Amira; Indra Maulana; Sukma Senjaya (Holistik Jurnal Kesehatan, 2022)
Background: Eating disorders are one of the psychiatric disorders with the highest mortality rates that cause serious psychological and medical consequences. Eating disorders are closely related to weight problems that affect the increase in suicidal ideation.Purpose: To determine the relationship between eating disorders and suicidal behavior in adolescents.Method: A scoping review by searching for articles using the Pubmed, ScienceDirect, and Wiley databases. The keywords used in searching the article were adolescent or adolescence or teen and eating disorder or compulsive eating or anorexia nervosa and suicidal tendencies or suicidal behaviors and relation or relative.Results: Sorting obtained six articles according to the inclusion and exclusion criteria that explained the causes of eating disorders, namely alcohol abuse, gender, mental illness, and closely related to suicidal ideation.Conclusion: Eating disorders and suicidal behavior are related to each other.Keywords: Eating disorders; Suicidal behavior; Adolescent.Pendahuluan: Gangguan makan merupakan salah satu gangguan kejiwaan dengan tingkat mortalitas tertinggi yang menimbulkan akibat psikologis dan medis serius. Gangguan makan erat kaitannya dengan permasalahan berat badan sehingga mempengaruhi peningkatan ide bunuh  diri.Tujuan: Untuk mengetahui hubungan eating disorder dengan suicidal behaviour pada remaja.Metode: Scoping review dengan pencarian artikel menggunakan database Pubmed, ScienceDirect dan Wiley. Kata kunci yang digunakan dalam mencari artikel yaitu adolescent or adolescence or teen and eating disorder or compulsive eating or anorexia nervosa and suicidal tendencies or suicidal behaviors and relation or relative.Hasil: Didapatkan enam artikel sesuai dengan kriteria inklusi dan eksklusi yang memaparkan penyebab gangguan makan yaitu penyalahgunaan alkohol, jenis kelamin, penyakit kejiwaan, serta erat kaitannya dengan ide bunuh diri.Simpulan: Eating disorder dengan suicidal behaviour saling berhubungan satu sama lain.